A method for modifying a lithium-rich manganese-based positive electrode material with a molybdenum carbide heterojunction coating

CN117602684BActive Publication Date: 2026-10-16GEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311665301.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-06
Publication Date
2026-10-16
Estimated Expiration
2043-12-06

AI Technical Summary

Technical Problem

[0006]上述方案制得富锂锰基正极材料采用掺杂的方法对富锂锰基正极材料进行改性,虽然掺杂可有效改善容量衰减、电压衰减或倍率性能,但它们只能抑制其中一种破坏性挑战,而彼此之间没有协同作用

Benefits of technology

[0032] (1) This invention utilizes a simple one-step surface treatment technique to construct a lithium-rich manganese-based cathode material with molybdenum doping and molybdenum carbide coating on its surface. This simple technique of constructing molybdenum doping and carbide coating on the surface enables the lithium-rich manganese-based cathode to simultaneously achieve high rate performance, suppressed voltage decay, and excellent long-term cycle stability. More importantly, this method is simple, low-cost, and highly reproducible, making it very suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117602684B_ABST
    Figure CN117602684B_ABST
Patent Text Reader

Abstract

The application provides a modification method of a molybdenum carbide heterojunction coating on a lithium-rich manganese-based positive electrode material, and the modification method comprises the following steps: (1) mixing a lithium-rich manganese-based precursor and a lithium source, and sintering to obtain a sintered material; (2) mixing the sintered material with a carbon source and a molybdenum source, and performing calcination treatment to obtain the lithium-rich manganese-based positive electrode material. Through a simple one-step surface treatment technology, molybdenum elements are doped in the surface layer of the lithium-rich manganese-based positive electrode material, and a molybdenum carbide coating layer is coated. This simple technology of constructing molybdenum doping and carbide coating on the surface enables the lithium-rich manganese-based positive electrode to simultaneously achieve high rate performance, inhibit voltage attenuation and excellent long-term cycle stability. More importantly, the method is simple, low in cost and good in repeatability, and is very suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery technology and relates to a method for modifying lithium-rich manganese-based cathode materials with a molybdenum carbide heterojunction coating. Background Technology

[0002] In recent years, lithium-rich cathode materials with dual redox centers of transition metals and oxygen redox reactions have attracted much attention, offering capacities exceeding 250 mAh / g. Besides traditional cathode materials, the unique Li-O-Li structure in lithium-rich cathode materials triggers reversible anionic redox reactions, resulting in high capacity. Among various lithium-rich cathodes, lithium-rich manganese oxide (LRMO) cathode materials, in addition to excellent electrochemical performance, also exhibit outstanding sustainability, making them a promising candidate cathode material. The non-toxicity of manganese (Mn) and its highest crustal abundance (~950 ppm) endow LRMO with environmental friendliness and low cost.

[0003] Due to the high operating voltage, lithium-rich manganese-based substrate oxides also experience undesirable cathode-electrolyte interface reactions, leading to electrolyte decomposition, transition metal ion migration, surface corrosion, and cathode dissolution. This further exacerbates the degradation in rate capability and cycle life. All of these problems severely hinder the large-scale application of lithium-rich manganese-based substrate oxides in electric vehicles.

[0004] CN113788500A discloses a method for surface modification of lithium-rich manganese-based cathode materials and the lithium-rich manganese-based cathode materials themselves. The surface modification method of this application includes mixing the lithium-rich manganese-based cathode material with a stannous salt solution, reacting at a constant temperature of 50-95℃ for 2 min-20 h under stirring conditions; filtering the reaction product at the constant temperature, washing and drying the filtered solid, and sintering at 300-800℃ for 30 min-4 h to obtain the surface-modified lithium-rich manganese-based cathode material.

[0005] CN111640931A discloses a method for preparing lithium-rich manganese-based cathode material, including the following steps: S1, preparing magnesium-doped precursor by carbonate co-precipitation: dissolving nickel salt, manganese salt and magnesium salt in water to obtain a mixed metal salt solution, and separately feeding the solution and precipitant solution into a reaction vessel, adjusting the pH value with a complexing agent, reacting for 24-120 hours to generate a precipitate, and then washing, drying, pulverizing and sieving the precipitate to obtain the precursor; S2, mixing and calcining the precursor with a lithium source: after fully grinding and mixing the precursor and the lithium source, sintering to obtain the cathode material.

[0006] The lithium-rich manganese-based cathode material prepared by the above scheme is modified by doping. Although doping can effectively improve capacity decay, voltage decay or rate performance, it can only suppress one of the destructive challenges and there is no synergistic effect between them. Summary of the Invention

[0007] The purpose of this invention is to provide a method for modifying lithium-rich manganese-based cathode materials with a molybdenum carbide heterojunction coating. This invention utilizes a simple one-step surface treatment technique to dope molybdenum onto the surface of the lithium-rich manganese-based cathode material and then coat it with a molybdenum carbide coating. This simple technique of constructing molybdenum doping and carbide coating on the surface enables the lithium-rich manganese-based cathode to simultaneously achieve high rate performance, suppressed voltage decay, and excellent long-term cycle stability. More importantly, this method is simple, low-cost, and highly reproducible, making it very suitable for large-scale production.

[0008] To achieve this objective, the present invention adopts the following technical solution:

[0009] In a first aspect, the present invention provides a method for modifying lithium-rich manganese-based cathode materials with a molybdenum carbide heterojunction coating, the modification method comprising the following steps:

[0010] (1) A lithium-rich manganese-based precursor and a lithium source are mixed and sintered to obtain a sintered material;

[0011] (2) The calcined material is mixed with a carbon source and a molybdenum source, and then calcined to obtain the lithium-rich manganese-based cathode material.

[0012] This invention utilizes a one-step surface treatment technique to prepare a lithium-rich manganese-based cathode material with a molybdenum-doped core and a molybdenum carbide coating on the outer layer. Molybdenum doping in the core improves the material's rate performance, while the molybdenum carbide coating provides acid and alkali resistance and corrosion resistance. This helps protect the migration of metal ions on the cathode particle surface, mitigating capacity and voltage decay. Furthermore, the small contact angle between molybdenum carbide and the electrolyte promotes sufficient contact between the cathode material and the electrolyte, enhancing the cycle performance of the lithium-rich manganese-based cathode.

[0013] Preferably, the chemical formula of the lithium-rich manganese-based precursor in step (1) is Ni x Co y Mn 1-x-y (OH)₂, where 0.4 ≥ x > 0.2, y < 0.1;

[0014] Preferably, the total molar ratio of metal elements in the lithium-rich manganese-based precursor to the molar ratio of lithium elements in the lithium source is 1:(1.3 to 1.6), for example: 1:1.3, 1:1.35, 1:1.4, 1:1.5 or 1:1.6, etc.

[0015] Preferably, the lithium source includes lithium carbonate and / or lithium hydroxide.

[0016] Preferably, the sintering temperature in step (1) is 800 to 1000°C, for example: 800°C, 850°C, 900°C, 950°C or 1000°C.

[0017] Preferably, the sintering time is 10 to 14 hours, for example: 10 hours, 11 hours, 12 hours, 13 hours or 14 hours.

[0018] Preferably, the carbon source in step (2) includes glucose.

[0019] Preferably, the molybdenum source includes MoO3.

[0020] Preferably, the mass of the carbon source in step (2) is 3 to 20% of the mass of the calcined material, for example: 3%, 5%, 8%, 10%, 12%, 15% or 20%, etc.

[0021] Preferably, the mass of the molybdenum source is 1 to 10% of the mass of the calcined material, for example: 1%, 2%, 3%, 5%, 7%, 8% or 10%, etc.

[0022] Preferably, the calcination temperature in step (2) is 300 to 500°C, for example: 300°C, 350°C, 400°C, 450°C or 500°C.

[0023] Preferably, the calcination treatment time is 2 to 6 hours, for example: 2 hours, 3 hours, 4 hours, 5 hours or 6 hours.

[0024] Preferably, the atmosphere for the calcination treatment includes nitrogen and / or argon.

[0025] In a second aspect, the present invention provides a lithium-rich manganese-based cathode material, which is prepared by the modification method described in the first aspect.

[0026] Preferably, the lithium-rich manganese-based cathode material includes a doped lithium-rich manganese-based core and a molybdenum carbide coating layer disposed on the surface of the doped lithium-rich manganese-based core.

[0027] Preferably, the surface layer of the doped lithium-rich manganese-based core contains molybdenum.

[0028] The lithium-rich manganese-based cathode material of this invention has a core surface layer doped with molybdenum, which can effectively improve the rate performance of the material. The outer molybdenum carbide coating layer has acid and alkali resistance and corrosion resistance, which helps to protect the migration of metal ions on the surface of the cathode particles and improve the problems of capacity decay and voltage decay. At the same time, it achieves high rate performance, suppressed voltage decay and excellent long-term cycle stability.

[0029] Thirdly, the present invention provides a positive electrode sheet comprising the lithium-rich manganese-based positive electrode material as described in the second aspect.

[0030] Fourthly, the present invention provides a lithium-ion battery comprising a positive electrode as described in the third aspect.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) This invention utilizes a simple one-step surface treatment technique to construct a lithium-rich manganese-based cathode material with molybdenum doping and molybdenum carbide coating on its surface. This simple technique of constructing molybdenum doping and carbide coating on the surface enables the lithium-rich manganese-based cathode to simultaneously achieve high rate performance, suppressed voltage decay, and excellent long-term cycle stability. More importantly, this method is simple, low-cost, and highly reproducible, making it very suitable for large-scale production.

[0033] (2) The discharge capacity of the battery made of the lithium-rich manganese-based cathode material described in this invention can reach more than 246.84 mAh / g, the capacity retention rate is more than 95.5% after 50 weeks, and the capacity retention rate is more than 93.25% after 100 weeks. Attached Figure Description

[0034] Figure 1 This is a thermodynamic calculation diagram of molybdenum carbide formation during the preparation of the lithium-rich manganese-based cathode material according to an embodiment of the present invention. Detailed Implementation

[0035] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.

[0036] The lithium-rich manganese-based precursors used in the embodiments and comparative examples of this invention were prepared by the following method:

[0037] First, nickel salt and manganese salt are added to a certain volume of aqueous solution according to stoichiometric ratio. Then, a co-precipitation method is used to prepare the product with the chemical formula Ni. 0.25 Mn 0.75 (OH)2 lithium-rich manganese-based hydroxide precursor.

[0038] Example 1

[0039] This embodiment provides a lithium-rich manganese-based cathode material. The thermodynamic calculation diagram of molybdenum carbide formation during the preparation process of the lithium-rich manganese-based cathode material is shown below. Figure 1 As shown, the preparation method of the lithium-rich manganese-based cathode material is as follows:

[0040] (1) The lithium-rich manganese-based precursor Ni 0.25 Mn 0.75 (OH)2 was mixed with lithium hydroxide at a lithium ratio of Li / TM = 1.5 and sintered at 900°C for 12 hours to obtain a sintered material;

[0041] (2) The calcined material is uniformly mixed with 10wt% glucose and 2wt% MoO3. The mixed sample is placed in a tube furnace and calcined at 500°C for 3 hours under an argon atmosphere to obtain the lithium-rich manganese-based cathode material.

[0042] Example 2

[0043] This embodiment provides a lithium-rich manganese-based cathode material. The thermodynamic calculation diagram of molybdenum carbide formation during the preparation process of the lithium-rich manganese-based cathode material is shown below. Figure 1 As shown, the preparation method of the lithium-rich manganese-based cathode material is as follows:

[0044] (1) The lithium-rich manganese-based precursor Ni 0.25 Mn 0.75 (OH)2 was mixed with lithium hydroxide at a lithium ratio of Li / TM = 1.5 and sintered at 800°C for 14 hours to obtain a sintered material;

[0045] (2) The calcined material is uniformly mixed with 8wt% glucose and 4wt% MoO3. The mixed sample is placed in a tube furnace and calcined at 400°C for 4 hours under an argon atmosphere to obtain the lithium-rich manganese-based cathode material.

[0046] Example 3

[0047] This embodiment provides a lithium-rich manganese-based cathode material. The thermodynamic calculation diagram of molybdenum carbide formation during the preparation process of the lithium-rich manganese-based cathode material is shown below. Figure 1 As shown, the preparation method of the lithium-rich manganese-based cathode material is as follows:

[0048] (1) The lithium-rich manganese-based precursor Ni 0.25 Mn 0.75 (OH)2 was mixed with lithium hydroxide at a lithium ratio of Li / TM = 1.5 and sintered at 1000℃ for 10 hours to obtain a sintered material;

[0049] (2) The calcined material is uniformly mixed with 15wt% glucose and 8wt% MoO3. The mixed sample is placed in a tube furnace and calcined at 500°C for 2 hours under an argon atmosphere to obtain the lithium-rich manganese-based cathode material.

[0050] Example 4

[0051] This embodiment provides a lithium-rich manganese-based cathode material. The thermodynamic calculation diagram of molybdenum carbide formation during the preparation process of the lithium-rich manganese-based cathode material is shown below. Figure 1 As shown, the preparation method of the lithium-rich manganese-based cathode material is as follows:

[0052] (1) The lithium-rich manganese-based precursor Ni 0.25 Mn 0.75(OH)2 was mixed with lithium hydroxide at a lithium ratio of Li / TM = 1.5 and sintered at 900°C for 11 hours to obtain a sintered material;

[0053] (2) The calcined material is uniformly mixed with 5wt% glucose and 2wt% MoO3. The mixed sample is placed in a tube furnace and calcined at 400°C for 4 hours under an argon atmosphere to obtain the lithium-rich manganese-based cathode material.

[0054] Example 5

[0055] The only difference between this embodiment and Embodiment 1 is that the mass of the carbon source is 3% of the mass of the calcined material; all other conditions and parameters are exactly the same as in Embodiment 1.

[0056] Example 6

[0057] The only difference between this embodiment and Embodiment 1 is that the mass of the carbon source is 20% of the mass of the calcined material; all other conditions and parameters are exactly the same as in Embodiment 1.

[0058] Example 7

[0059] The only difference between this embodiment and Embodiment 1 is that the mass of the molybdenum source is 1% of the mass of the calcined material; all other conditions and parameters are exactly the same as in Embodiment 1.

[0060] Example 8

[0061] The only difference between this embodiment and Embodiment 1 is that the mass of the molybdenum source is 10% of the mass of the sintered material; all other conditions and parameters are exactly the same as in Embodiment 1.

[0062] Comparative Example 1

[0063] The only difference between this comparative example and Example 1 is that a calcined material is directly used as the positive electrode material; all other conditions and parameters are exactly the same as in Example 1.

[0064] Comparative Example 2

[0065] The only difference between this comparative example and Example 1 is that no carbon source is added; all other conditions and parameters are exactly the same as in Example 1.

[0066] Comparative Example 3

[0067] The only difference between this comparative example and Example 1 is that no molybdenum source is added; all other conditions and parameters are exactly the same as in Example 1.

[0068] Performance testing:

[0069] All test results are for button cell testing. The specific steps are as follows: First, the active material, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are dissolved in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1. The slurry is then homogenized at room temperature using a homogenizer in a multi-stage mode. Next, the ground slurry is coated onto A1 foil using a coater and dried in a vacuum drying oven at 80℃ for 8 hours. Finally, the aluminum foil is stamped into 1.13cm diameter pieces. 2 The positive electrode was obtained by forming a circular shape. The resulting electrode sheet was used as the positive electrode, the lithium metal sheet as the counter electrode, and a porous polypropylene membrane (Celgard 2400, USA) was used as a separator to separate the positive and counter electrodes. The CR-2032 battery was assembled in a glove box filled with Ar gas. Battery testing was performed using a battery testing system (Landian CT2001A, Wuhan, China). First, the battery was activated three times at a rate of 0.1C within a voltage range of 2.0–4.8V. Then, the activated coin cells were subjected to cycle and rate tests at different rates within the same voltage range. The test results are shown in Table 1.

[0070] Table 1

[0071]

[0072]

[0073] As can be seen from Table 1, as obtained from Examples 1-4, the discharge capacity of the battery made from the lithium-rich manganese-based cathode material prepared by the modification method of the present invention can reach more than 246.84 mAh / g, the capacity retention rate after 50 weeks is more than 95.5%, and the capacity retention rate after 100 weeks is more than 93.25%.

[0074] A comparison of Examples 1 and 5-6 shows that the amount of carbon source added in the modification method of the present invention affects its performance. Controlling the mass of the carbon source to 5-15% of the mass of the calcined material results in a cathode material with better performance. If the amount of carbon source added is too low, the molybdenum carbide coating layer on the surface of the lithium-rich manganese-based cathode will be thin, making it difficult to maintain the stability of the material's electrochemical performance. If the amount of carbon source added is too high, it will result in more floating carbon on the material surface, which is not conducive to the capacity of the lithium-rich manganese-based cathode.

[0075] A comparison of Examples 1 and 7-8 shows that the amount of molybdenum source added in the modification method of the present invention affects its performance. Controlling the mass of the molybdenum source to 2-8% of the mass of the calcined material results in a cathode material with better performance. If the amount of molybdenum source added is too low, the amount of molybdenum doping and molybdenum carbide content in the sample will decrease, further leading to a decrease in the capacity of the lithium-rich manganese cathode. If the amount of molybdenum source added is too high, the amount of molybdenum doping in the sample will be too high, i.e., the amount of impurities will be high, resulting in severe lattice distortion of the material, ultimately making it difficult for the lithium-rich manganese cathode to achieve its full potential.

[0076] As can be seen from the comparison between Example 1 and Comparative Examples 1-3, the lithium-rich manganese-based cathode material of the present invention has a core surface doped with molybdenum and an outer layer coated with molybdenum carbide. The molybdenum doping in the core improves the rate performance of the material, while the outer molybdenum carbide coating provides acid and alkali resistance and corrosion resistance. This helps protect the migration of metal ions on the surface of the cathode particles, improving capacity and voltage decay. Furthermore, the small contact angle between molybdenum carbide and the electrolyte facilitates sufficient contact between the cathode material and the electrolyte, increasing the cycle performance of the lithium-rich manganese-based cathode.

[0077] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for modifying lithium-rich manganese-based cathode materials with a molybdenum carbide heterojunction coating, characterized in that, The modification method includes the following steps: (1) A lithium-rich manganese-based precursor and a lithium source are mixed and sintered to obtain a sintered material; (2) The calcined material is mixed with a carbon source and a molybdenum source, and then calcined to obtain the lithium-rich manganese-based cathode material; The carbon source in step (2) includes glucose, and the molybdenum source includes MoO3; In step (2), the mass of the carbon source is 5-15% of the mass of the calcined material, and the mass of the molybdenum source is 2-8% of the mass of the calcined material. The calcination temperature in step (2) is 300~500℃; The calcination treatment time is 2-6 hours; The lithium-rich manganese-based cathode material includes a doped lithium-rich manganese-based core and a molybdenum carbide coating layer disposed on the surface of the doped lithium-rich manganese-based core. The surface layer of the doped lithium-rich manganese-based core contains molybdenum.

2. The modification method as described in claim 1, characterized in that, The chemical formula of the lithium-rich manganese-based precursor in step (1) is Ni x Co y Mn 1-x-y (OH)2, where 0.4 ≥ x > 0.2 and y < 0.

1.

3. The modification method as described in claim 2, characterized in that, The total molar amount of metal elements in the lithium-rich manganese-based precursor and the molar ratio of lithium elements in the lithium source are 1:(1.3~1.6).

4. The modification method as described in claim 1, characterized in that, The lithium source includes lithium carbonate and / or lithium hydroxide.

5. The modification method as described in claim 1, characterized in that, The sintering temperature in step (1) is 800~1000℃.

6. The modification method as described in claim 1, characterized in that, The sintering time is 10-14 hours.

7. The modification method as described in claim 1, characterized in that, The atmosphere for the calcination treatment includes nitrogen and / or argon.

8. A lithium-rich manganese-based cathode material, characterized in that, The lithium-rich manganese-based cathode material is prepared by the modification method described in any one of claims 1-7; The lithium-rich manganese-based cathode material includes a doped lithium-rich manganese-based core and a molybdenum carbide coating layer disposed on the surface of the doped lithium-rich manganese-based core. The surface layer of the doped lithium-rich manganese-based core contains molybdenum.

9. A positive electrode sheet, characterized in that, The positive electrode comprises the lithium-rich manganese-based positive electrode material as described in any one of claims 8.

10. A lithium-ion battery, characterized in that, The lithium-ion battery includes the positive electrode as described in claim 9.

Citation Information

Patent Citations

  • Lithium-rich manganese-based positive electrode material surface modification method and lithium-rich manganese-based positive electrode material

    CN113788500A

  • Lithium supplement material and preparation method and application thereof

    CN116779806A